2017
DOI: 10.1002/trtr.1634
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Scientific Metaphors Through Informational Text Read‐Alouds

Abstract: Scientific metaphors presented in informational texts can help elementary students develop conceptual understandings of complex scientific processes and topics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Additionally, reading is also a basic link in cultivating students' ST. Tsabari and Yarden (2005) has proved that students' good independent reading habits are the premise of scientific inquiry ability. At the same time, Barnes and Oliveira (2018) also confirmed that text reading and narrative logic can effectively help primary school students understand scientific metaphors and develop ST. Therefore, language art (reading, writing, and listening) may be a unique attribute that affects the development of students' ST.…”
Section: Influential Factors Of Scientific Thinkingmentioning
confidence: 55%
“…Additionally, reading is also a basic link in cultivating students' ST. Tsabari and Yarden (2005) has proved that students' good independent reading habits are the premise of scientific inquiry ability. At the same time, Barnes and Oliveira (2018) also confirmed that text reading and narrative logic can effectively help primary school students understand scientific metaphors and develop ST. Therefore, language art (reading, writing, and listening) may be a unique attribute that affects the development of students' ST.…”
Section: Influential Factors Of Scientific Thinkingmentioning
confidence: 55%
“…Case method teaching typically offer well-crafted scenarios where students practice analytical thinking within constraints and presets of past, place and protagonists directly influenced by real organizations. These business cases play an important role in building skills of case-based observation, analysis, and summarization (Barnes et al, 1994;Wasserman, 1994). Their value is further derived from a cohort' s shared understanding and exploration of key events leading to generalizable recommendations -which are facilitated by the academic case authors.…”
Section: From Business Cases To Business Designsmentioning
confidence: 99%